Images, paysages, gestes, mondes. La dialectique bachelardienne des musiques contemporaines - Maestri, Eric (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Bachelard’s subtle links between the words of poets and reality open up spaces of resonance. And these spaces are central to the concerns of contemporary musicians. Indeed, recording techniques and the manipulation of sound matter create new realities, enabling musicians to compose the dialectic between reality and dream. A parallel reading of La Dialectique de la durée in particular, and the poetic and theoretical texts of certain contemporary musicians, will enable us to develop this theme. Bachelard is interpreted as a musician who listens to the silent spaces at the margins of sound events and their spatial and spiritual resonances.